Design of the Control System for a Hexapod Walking Robot - Jin Bo; Zhao Li-jun; Zhang Jia-Lin; Chen Cheng; Hu Sha (2011 Second International Conference on Digital Manufacturing and Automation, 2011)
In this paper, the structure of a mammal-Like hexapod walking robot is presented and the joint trajectory planning method of tripod gait is analyzed. The motions with 12 degrees of freedom (DOF) for the robot are reaLized by 12 rudder servos. The control pulse width send to each servomotor determines the motor position. The control system is composed of two layers with different function. Coordination-layer is a PC for regulating the whole system. It calculates each joint's expected trajectory according to user's definitions, and then transmits the objective position data to execution-layer through serial port. The execution-layer uses a ARM7 based microprocessor LPC2132 as core controller. It adopts time sLicing method and three timer-interrupt programs are employed to drive 12 rudder servos coordinately for reaLizing the steady walking of the robot.